Job shop scheduling problem (JSSP) - Abdullah, Nurul Azma (2004)
The job shop scheduling problem is a special case of the general shop in which each job i consists of n tasks Tij with processing times pij (j=l, ... ,m) where Tij has to be processed on machine Mij, and the tasks have to be scheduled in predetermined given order. The job shop problem is to find a feasible schedule, for example, to determine starting times for each task for all jobs to minimize the objective function of the problem. This paper concerns in evaluate the performance of two techniques of dispatching rules which are Earliest Due Date (EDD) and Slack per Remaining Operation (SRO). The schedules are constructed based of these two heuristics. The performance of these techniques open a study on improvement techniques such as metaheuristics techniques which use a local search as a base and most recent technique introduced by David E. Joslin and David P. Clements in 1998, Squeaky Wheel which is believed to improve the schedule generated by greedy algorithm technique. Keywords: job shop scheduling problem, dispatching rules, earliest due date, slack per remaining operation, local search, squeaky wheel.